Experimental and Simulation Analysis of Hydrogen Permeation Performance of Pd/Ag Permeator Used for Tritium Processing. (3rd March 2020) - Huang, Yu; Lu, Gaofeng; Zeng, Youshi; Qian, Nan; Chu, Xinxin; Wang, Guanghua; Wu, Shengwei; Liu, Wei
Abstract: Since the Pd/Ag membrane has a permselectivity for hydrogen isotopes, a permeator with a Pd/Ag membrane is developed to separate tritium from inert gases. First, a permeation experiment of pure H2 was carried out to determine the pressure exponent and the rate-determining step of permeation. It was found that the diffusion of H2 through the Pd membrane was the rate-determining step. Then, the separation of H2 from H2 -Ar gas mixtures was carried out on the permeator to simulate the separation of tritium. Moreover, numerical simulation was utilized to study the concentration distribution of H2 in the permeator. The permeability of the Pd/Ag membrane was determined comparing the simulation results with the experimental data. The permeation flux of H2 through the Pd/Ag membrane is affected by permeability, the volume fraction of Ar in the feed gas, and the flow rate of the feed gas. In the condition of high permeability and Ar volume fraction, a phenomenon known as concentration polarization occurred. It can strongly affect the permeation of H2 . Based on these results, an optimized design of the Pd/Ag permeator can be made to effectively separate tritium from other gases.